Evaluation of adipokines concentrations in plasma, peritoneal, and endometrioma fluids in women operated on for ovarian endometriosis - Wójtowicz, Mariusz; Zdun, Dariusz; Owczarek, Aleksander Jerzy; Skrzypulec-Plinta, Violetta; Olszanecka-Glinianowicz, Magdalena (Frontiers in Endocrinology, 2023)
Introduction: Some studies indicate the role of selected adipokines in the development of endometriosis. However, a comprehensive assessment of plasma, peritoneal, and endometrioma fluid adipokine concentrations in women with ovarian endometriosis has not yet been performed. Therefore, this study aimed to analyze plasma, peritoneal, and endometrioma fluid selected adipokines concentrations in women operated on for ovarian endometriosis.A cross-sectional cohort study involved 56 women operated on for ovarian endometriosis. Body mass, height, and waist circumference were measured, as well as BMI being calculated. Plasma, peritoneal, and endometrioma fluid adiponectin, leptin, omentin resistin, RBP4, and visfatin/NAMPT were determined by ELISA.The highest plasma levels of adiponectin, leptin, omentin and RBP4 in the endometrioma and peritoneal fluids were found, while, levels of resistin and visfatin/NAMPT were significantly higher in endometrioma fluid compared to plasma and peritoneal fluid. In addition, levels of visfatin/NAMPT were significantly higher in peritoneal fluid than in plasma.There were also positive correlations between leptin, RBP4, and adiponectin levels in endometrioma and peritoneal fluids (r = 0.28; p < 0.05; r = 0.31; p < 0.05; r= 0.32; p < 0.05, respectively). There were no associations between adipokine levels in plasma, endometrioma, and peritoneal fluid and endometriosis stage.Our results show that visfatin/NAMPT and resistin may be locally secreted in endometrioma related to inflammation regardless of the stage of endometriosis.